Zinc oxide nanoparticles enhanced rice yield, quality, and zinc content of edible grain fraction synergistically - Mi, Kailiang; Yuan, Xijun; Wang, Qianyue; Dun, Canping; Wang, Rui; Yang, Shuo; Yang, Yanju; Zhang, Hongcheng; Zhang, Haipeng (Frontiers in Plant Science, 2023)
Abstract: Zinc oxide nanoparticles (ZnO NPs) has been widely used in agriculture as a new type of Zn fertilizer, and many studies were conducted to evaluate the effect of ZnO NPs on plant growth. However, there are relatively few studies on the effects of application methods and appropriate dosages of ZnO NPs on rice yield, quality and grain Zn content and distribution. Therefore, in the 2019 and 2020, field trials were conducted with six ZnO NPs basal application dosages of no ZnO NPs, 3.75 kg hm-2, 7.5 kg hm-2, 15 kg hm-2, 30 kg hm-2 and 60 kg hm-2, and the effects of ZnO NPs application on rice yield, quality, grain Zn content and distribution were investigated. The results demonstrated that applying ZnO NPs in Zn-deficient soils (available Zn < 1.0 mg kg-1) increased rice grain yield by 3.24%-4.86% and 3.51%-5.12% in 2019 and 2020, respectively. In addition, ZnO NPs improved the quality of rice by increasing the head milling rate, reducing chalky grain percentage, increasing the taste value and breakdown of rice. In terms of Zn accumulation in rice, ZnO NPs application significantly increased the Zn content in both milled rice and brown rice, compared to no Zn treatment, in 2019 and 2020, Zn content in milled rice significantly increased by 20.46%-41.09% and 18.11%-38.84%, respectively, and in brown rice significantly increased by 25.78%-48.30% and 20.86%-42.00%, respectively. But the Zn fertilizer utilization gradually decreased with increasing ZnO NPs application dosage. From the perspective of yield, rice quality, Zn fertilizer utilization and Zn accumulation, basal application of 7.5-30 kg hm-2 ZnO NPs is beneficial for rice yield and quality improvement and rice Zn accumulation. This study effectively demonstrated that ZnO NPs could be a potential high‐performed fertiliser for enhancing rice yield, quality and zinc content of edible grain fraction synergistically.